PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS IX SMP NEGERI 2 PARIAMAN - Fadhila, Talitha (Jurnal Edukasi dan Penelitian Matematika, 2024)
One measure of a successful learning process is the results that students take away from it. For learning to be considered effective, there must be an improvement in pupils' knowledge relative to their prior performance. However, this is still on the low side for class IX at SMP Negeri 2 Pariaman in FY 2024/2025. The use of the cooperative model known as Student Teams Achievement Division as one of the efforts to address this issue The purpose of the research is to explain the development of studens learning achievements through the STAD model. Additionally, it aims to investigate whether the mathematics learning outcomes of students who learn using the STAD cooperative model are better than those of students who learn with the conventional learning model. Quasi-eksperimental research through a posttest-only control group design. Quizzes and test are used as research tools. The research results show that there is a positive development in students mathematics learning outcomes when using the STAD paradigm in the classroom. The null hypothesis (H0) is rejected because the hypothesis test results using the t-test yielded a P-value of 0,003, which is less than . The results show that the STAD model produces superior learning outcomes compared to conventional learning in the ninth grade at SMP Negeri 2 Pariaman.Keywords– Mathematics Learning Achievement, STAD Learning Model, Konvensional Learning